The Process Of Advocacy In Romanian Public Policy - Gurgu, Elena; ZORZOLIU, Raluca Ileana (Annals of Spiru Haret University. Economic Series, 2016)
Influencing public policy in favor of interest groups can be achieved through advocacy associations legally constituted whose mission is to: promovate professional excellence in the application of advanced practices of advocacy, strengthen civil society participation in development of public policies and continuously develop policies to private firms.. Through advocacy associations can uphold and enforce the values of entrepreneurship and free enterprise. Any resource used in advocacy efforts associations should generate added value and impact, contribute to the progress, development and improved quality of life. Advocacy associations must primarily promotes technical and professional skills of advocacy for any civil society interested group with honesty, dignity, mutual respect, transparency and social responsibility in order to strengthen the system of participatory democracy to which they are signatories.